(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2022)
This study intends to determine whether audio-assisted repeated reading or oral repeated reading could really help the Grade 7 students in terms of accuracy, speed, and comprehension. Students who were rated as slow readers when the reading test was administered were selected. It aimed to answer the following: (1) To determine the level of learning in reading of the students in pretest according to accuracy, speed and comprehension before intervention is done; (2) To determine the level of learning in reading of the students in the posttest according to accuracy, speed, and comprehension after doing the intervention; 3) To determine if there is a significant difference in the posttest of students on audio-assisted repeated reading and oral repeated reading; and (4) To determine whether of the two strategies audio-assisted repeated reading or oral repeated reading helped slow readers improve their accuracy, speed, and comprehension. The study used a quasi-experimental design as the participants freely chose the strategy to be used. In the quantitative method for evaluating the results of the two strategies, normative comparison was used. Whereas in the qualitative method related to descriptive analysis, focus group discussion was used. Oral repeated reading and audio-assisted repeated reading were found to be effective because they increased students’ reading accuracy and speed. They will be able to keep up with all the subjects that require reading if their progress is continuous. Therefore, it is suggested to use it as an intervention to address other students with poor reading skills.